Poverty Situation of Cocoa Smallholders and Its Determinant in West Sulawesi, Indonesia - Nurlaela Nurlaela; Muhammad Arafat Abdullah (Hasanuddin University, 2017)
Poverty of cocoa smallhoders is still identifed as a serious issue in Indonesia. The general specific objectives of the research is to calculate the percentage of cocoa smallholders are living below the Provincial Poverty Line and identifying determinant affects poverty of smallholders. The research employed Head Count Index and Path Analysis. Results show that the percentage of cocoa farmers living below Poverty Line reached 65% in the province. Determinant factors affects poverty situation is education attainment of family member, access to price information, cocoa estate area, distance to school. It suggests that in order to reduce poverty of cocoa farmers need to improve children and education attainment, making school is more closer to the farmers community and develop cocoa estate area and connecting price information to the farmers.